“Implementación de un sistema de circuito cerrado, mediante IP, para mejorar el proceso de video vigilancia en el Bloque B de la Universidad Técnica de Cotopaxi Extensión La Maná”. - Pastuña Toapanta, Edwin Andres (2021)
This research work is based on the implementation of a closed-circuit system through the Internet Protocol which has as its sole and exclusive task to provide real-time and timely security to Block B of the Technical University of Cotopaxi in La Maná through video surveillance cameras that have a 360-degree rotation with the highest quality video. Through this system, all events and incidences that take place inside and outside Block B can be monitored, obtaining high-quality visual support and providing better security control, benefiting students, teachers, authorities, administrative and service personnel, other people who live in or commonly pass through this sector. For the implementation of the IP closedcircuit system, important parameters are considered such as camera sensitivity, the configuration of patterns in the cameras for monitoring, extended visual range, video recording time, and the extraction of information from the sequence of recorded videos through the camera queries, thus making it possible to know the facts or events at a given time using cuttingedge and innovative technology.